Pengaruh Moderasi Gender terhadap Niat Penggunaan Aplikasi Seabank di Kalangan Mahasiswa Yogyakarta dengan Analisis Model UTAUT2 - Wardhani, Aurelia Melinda Nisita; Handoyo, Emanuel Ristian (EXERO : Journal of Research in Business and Economics, 2024)
This study aims to analyze the moderating effect of gender on the intention to use the Seabank application among Yogyakarta university students using the Unified Theory Of Acceptance And Use Of Technology 2 (UTAUT2) model. The research method used is a quantitative survey by distributing questionnaires to 110 university students. The data obtained were analyzed using Structural Equation Modeling (SEM) techniques, while the analysis tool used was SmartPLS. The results showed that gender moderation was not significant in influencing the relationship between facilitating conditions, hedonic motivation, price value and habit on behavioral intention to use the Seabank application. This finding suggests that these factors influence usage intention independently of gender. The implication of this study is that digital financial application marketing strategies can be focused on increasing performance expectations and effort without the need to consider gender differences.